2018
DOI: 10.1159/000488228
|View full text |Cite
|
Sign up to set email alerts
|

Procoagulant Activity of Blood and Endothelial Cells via Phosphatidylserine Exposure and Microparticle Delivery in Patients with Diabetic Retinopathy

Abstract: Background/Aims: The mechanisms for thrombosis in diabetic retinopathy (DR) are complex and need to be further elucidated. The purpose of this study was to test phosphatidylserine (PS) exposure on microparticles (MPs) and MP-origin cells from the circulation and to analyze cell-/MP-associated procoagulant activity (PCA) in DR patients. Methods: PS-positive MPs and cells from healthy controls (n = 20) and diabetic patients (n = 60) were analyzed by flow cytometry and confocal microscopy. Clotting time and purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…The different ability of pEVs and monocytic EVs to support FXII-mediated thrombin generation might therefore rather be due to differences in their membrane composition. Based on the primary role of phosphatidylserine in supporting coagulation (Lentz, 2003;Ansari et al, 2016;Su et al, 2018), our data provide evidence that EVs from different sources or settings might differ regarding their exposure of phosphatidylserine. This is further supported by the data obtained with flow cytometric characterization of pEVs, rbcEVs, and mlEVs in the present work, showing higher density of phosphatidylserine on pEVs and rbcEVs as compared to mlEVs.…”
Section: Discussionmentioning
confidence: 82%
“…The different ability of pEVs and monocytic EVs to support FXII-mediated thrombin generation might therefore rather be due to differences in their membrane composition. Based on the primary role of phosphatidylserine in supporting coagulation (Lentz, 2003;Ansari et al, 2016;Su et al, 2018), our data provide evidence that EVs from different sources or settings might differ regarding their exposure of phosphatidylserine. This is further supported by the data obtained with flow cytometric characterization of pEVs, rbcEVs, and mlEVs in the present work, showing higher density of phosphatidylserine on pEVs and rbcEVs as compared to mlEVs.…”
Section: Discussionmentioning
confidence: 82%
“…[36] Studies considered that the most notable reactome pathway of DR was “platelet degranulation.” [37] In addition, procoagulant activity in DR patients may be partly ascribed to phosphatidylserine exposure and microparticles release from blood and endothelial cells. [38] Thus, platelets contribute cooperatively to the hypercoagulable state of DR patients and play an important role in formation of DR.…”
Section: Discussionmentioning
confidence: 99%
“…71,72 Increased levels of PMPs and MMPs have been reported in patients with DR. 70,76 However, the presence of RMPs, EMPs, LMPs (specifically derived from polynuclear cells), and lymphocyte-derived MPs has also been observed in these patients. 77 Interestingly, it was also found that patients with proliferative DR, the more advanced form of DR, displayed the highest levels of RMPs, EMPs, and polynuclear cell-derived MPs compared with patients without DR. These findings suggest that patients with proliferative DR have more endothelial damage and greater risk of coagulation aberration.…”
Section: Diabetic Retinopathymentioning
confidence: 92%
“…These findings suggest that patients with proliferative DR have more endothelial damage and greater risk of coagulation aberration. 77 In addition, the authors also observed that the exposure of phosphatidylserine (PS) in MPs is significantly elevated in patients with DR. This increased PS exposure is believed to promote the procoagulant activity of MP in DR patients by facilitating the assembly of prothrombinase complexes and providing a binding site for factor Xa, thus contributing to increased thrombin generation.…”
Section: Diabetic Retinopathymentioning
confidence: 97%